2018
DOI: 10.1021/acscatal.7b04504
|View full text |Cite
|
Sign up to set email alerts
|

High Catalytic Activity of Pd1/ZnO(101̅0) toward Methanol Partial Oxidation: A DFT+KMC Study

Abstract: We perform density functional theory (DFT) calculations of the energetics for several pathways associated with methanol partial oxidation (MPO) reaction on singly distributed Pd on ZnO (Pd1/ZnO) and use them in kinetic Monte Carlo (KMC) simulations for elucidating reaction mechanism. We compare these results for Pd1/ZnO with those obtained for the same set of reactions on a 32-atom Pd16Zn16 nanocluster. Our KMC simulations show that Pd1/ZnO offers high, temperature-dependent selectivity (∼93%) for H2 productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 95 publications
(141 reference statements)
0
22
0
Order By: Relevance
“…In addition, we compared the NN bond lengths of the adsorbed N 2 molecule on the NRR catalysts with relatively good activities toward NRR, namely single Ti, Pt, W, Co, and Mo atoms supported by g‐C 3 N 4 . Interestingly, the NN bond lengths of the adsorbed N 2 molecule also shows a volcano shape (Figure b), which well resembles that of the limiting potential (Figure ) and suggests that the adsorbed N 2 molecule can be more sufficiently “activated” on W@C 3 N 4 than other catalysts.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…In addition, we compared the NN bond lengths of the adsorbed N 2 molecule on the NRR catalysts with relatively good activities toward NRR, namely single Ti, Pt, W, Co, and Mo atoms supported by g‐C 3 N 4 . Interestingly, the NN bond lengths of the adsorbed N 2 molecule also shows a volcano shape (Figure b), which well resembles that of the limiting potential (Figure ) and suggests that the adsorbed N 2 molecule can be more sufficiently “activated” on W@C 3 N 4 than other catalysts.…”
Section: Resultsmentioning
confidence: 52%
“…Such catalysts not only maximize the efficiency of metal usage to 100% and significantly reduce the metal cost, especially for noble metal catalysts, such as Au, Pt, Ir, and Pd, but also provide great potentials to achieve high activity and selectivity due to the high ratio of the low‐coordinated metal atoms . These advantages distinguish SACs from their corresponding bulk materials and nanoparticles, and SACs have already emerged as a new class of catalyst for a variety of important reactions, such as CO oxidation, methanol partial oxidation, water‐gas shift, selective hydrogenation of 1,3‐butadiene, some important organic reactions, such as oxidation, hydrogenation, CC coupling and reforming, electrocatalytic, or photocatalytic reactions …”
Section: Introductionmentioning
confidence: 99%
“…On the basis of computational studies, 26 methanol dehydrogenation is the rate-determining step for efficient production of H 2 through MPO over Pd−Zn/ZnO and pure ZnO. Their overall reaction barriers are 1.33 and 2.78 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…ZnO has been extensively studied in a great many of catalytic reactions, such as methanol synthesis, 25 methanol partial oxidation, 26 methanol steam reforming, 27,28 the water-gas shift reaction, 29 and the dehydrogenation of light alkanes. 17,30 To inhibit deactivation and improve the catalytic performance for a specific reaction, synthesis of composite oxides and modification of ZnO have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…27 Rawal et al also found that, in the methanol partial oxidation reaction, Pd1-ZnO showed remarkable and excellent catalytic performance compared to Pd16Zn16 and pristine ZnO( 1010 ), where they attributed the increased activity to the great influence of the singly dispersed Pd atom on the local environment of the active Zn sites. 26 Despite a great deal of research, it is still not clear how the doped single atoms would modify the electronic structure of the ZnO surface and how the two components actually function in the chemical reactions. More importantly, there are no rules based on simple physical properties that can be used to guide us in predicting the trend in the activity of the single-atom-doped ZnO catalysts.…”
Section: Introductionmentioning
confidence: 99%